FISH localization of the human Y-homolog of protein kinase PRKX (PRKY) to Yp11.2 and two pseudogenes to 15q26 and Xq12-->q13 - Schiebel, Katrin; Mertz, A.; Winkelmann, M.; Gläser, Birgitta; Schempp, Werner; Rappold, Gudrun (Cytogenetics and cell genetics, 1997)
Recently, we reported the isolation of a new subfamily of serine-threonine protein kinases. This subfamily was shown to consist of at least four members. Sequencing and FISH mapping of all 4 members now reveals that the Y-homolog (PRKY) of the previously mapped PRKX gene (Xp22.3) is located in Yp11.2, in close vicinity to AMELY. The other two copies reside on Xq12-->q13 (PRKXP2) and 15q26 (PRKXP1, containing CA repeat STS D15S87) and represent pseudogenes.
Elektronische Reproduktion der Druck-Ausgabe
Online: May 20, 2008
Gesehen am 29.03.2021